2016
DOI: 10.1186/s13012-016-0526-z
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a tailored intervention programme of cardiovascular risk management in general practices

Abstract: BackgroundA tailored implementation programme to improve cardiovascular risk management (CVRM) in general practice had little impact on outcomes. The questions in this process evaluation concerned (1) impact on counselling skills and CVRM knowledge of practice nurses, (2) their use of the various components of the intervention programme and adoption of recommended practices and (3) patients’ perceptions of counselling for CVRM.MethodsA mixed-methods process evaluation was conducted. We assessed practice nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Practice nurses received feedback training on motivational interviewing skills; motivational interviewing is considered a promising counselling technique (11). However, the primary analyses of this tailored implementation programme in a randomized trial (12) and a process evaluation (13) showed hardly any improvement in patient cardiovascular risk factors and practice nurses’ counselling skills.…”
Section: Introductionmentioning
confidence: 99%
“…Practice nurses received feedback training on motivational interviewing skills; motivational interviewing is considered a promising counselling technique (11). However, the primary analyses of this tailored implementation programme in a randomized trial (12) and a process evaluation (13) showed hardly any improvement in patient cardiovascular risk factors and practice nurses’ counselling skills.…”
Section: Introductionmentioning
confidence: 99%